Influencer : the new science of leading change - Grenny, Joseph, ....-; Maxfield, David, ....-; Patterson, Kerry, 1946- (New York : McGraw-Hill Education, 2013)
CHANGE YOUR COMPANY. CHANGE THE LIVES OF OTHERS. CHANGE THE WORLD.An INFLUENCER leads change. An INFLUENCER replaces bad behaviorswith powerful new skills. An INFLUENCER makes things happen. This is what it takes to be an INFLUENCER. Whether you're a CEO, a parent, or merely a person who wants to make a difference, you probably wish you hadmore influence with the people in your life. But most of us stop trying to make change happen because we believe itis too difficult, if not impossible. We learn to cope rather than learning to influence.
Includes bibliographical references (p. 301-310) and index.
Keywords: Influence (Psychology).; Interpersonal relations